Simulation of Weft Knitted Fabric Using Three-Dimensional Yarn Loops and Grid and Spring Mass Models - Haodong Hu; Tong Li; Wei Ke; Lijing Wang; Zhongmin Deng (Advances in Materials Science and Engineering)
The existing knitted fabric simulation methods cannot be effectively applied to three-dimensional (3D) modeling and simulation of weft knitted garments due to the lack of simple and convenient 3D dynamic simulation models for weft knitted fabrics. This paper presents a method of constructing a loop model by coupling the grid model with the spring mass model. The simulation of weft knitted fabric with real effects was achieved through the coupled model construction of the loop model combined with the yarn simulation generation algorithm and yarn collision response algorithm. The method presented in this paper can quickly and simply simulate the design of weft knitted clothing with loop structure. It provides a reference for the 3D simulation design of weft knitted fabric.